Dampak Citra TikTok Shop dan E-WOM terhadap Perilaku Belanja Online Gen-Z - Saputra, Al Mahfud; Fakhrurrazi; Mukhdasir (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine the influence of brand image and Electronic Word Of Mouth (e-WOM) on the attitudes and purchase intentions of Generation Z in Aceh when shopping at TikTok Shop. In this study, an online questionnaire was used to obtain the required information. Quota sampling was used to determine a sample of 200 consumers. Analysis with SmartPLS software through Structural Equation Modeling (SEM) was used to assess the measurement and structural models. The results of the study found that brand image, e-WOM, and consumer attitudes directly impact consumer intentions to shop online. Especially when the e-WOM obtained is positive. The attitude itself is directly influenced by brand image and e-WOM. However, consumer attitudes cannot mediate the relationship between brand image and e-WOM that affects purchase intentions. This study can contribute to online retailers in Aceh, significantly improving consumer attitudes at TikTok Shop by aligning products sold and purchased by consumers to minimize negative comments.